Physiological Response at Different Plant Development Stages in Glycine max Exposed to Elevated CO2 Concentrations and Fly Ash-Amended Soils - Rodriguez, Judith Hebelen (2015)
Increasing concentrations of carbon dioxide and heavy metals in soils through pollution are serious problems worldwide. In the present study, we investigated the impacts of elevated atmospheric CO2 and fly ash (FA)-amended soil on the physiological response (chlorophyll content, non-structural carbohydrates, oil and total proteins) of soybean [Glycine max (L.) Merrill] at three growth stages (vegetative, reproductive and maturity). An increase in plant growth and biomass was observed at elevated CO2 and for moderate concentrations of FA in amended soils in all development plant stages. In contrast to these results, a different response pattern was found for the chlorophyll content and non-structural carbohydrates in relation to the developmental stage, showing that even though in the vegetative growth stage the highest concentration of chlorophylls corresponded to elevated CO2 conditions. An opposite result was observed during the grain filling stage (reduction of chlorophylls of 15 % at ambient CO2 conditions for the treatments 10, 15, and 25 % of FA), which probably is related with the distribution of nutrients at this stage. Regarding to oil and total protein content an increase was observed at elevated CO2 and high concentrations of FA in amended soils. Our findings demonstrate that elevated CO2 and FA-amended soils alter the physiological response of soybean affecting the crop quality.